2019
DOI: 10.1038/s41598-019-43414-0
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower mosaic virus transactivator protein (TAV) can suppress nonsense-mediated decay by targeting VARICOSE, a scaffold protein of the decapping complex

Abstract: During pathogenesis, viruses hijack the host cellular machinery to access molecules and sub-cellular structures needed for infection. We have evidence that the multifunctional viral translation transactivator/viroplasmin (TAV) protein from Cauliflower mosaic virus (CaMV) can function as a suppressor of nonsense-mediated mRNA decay (NMD). TAV interacts specifically with a scaffold protein of the decapping complex VARICOSE (VCS) in the yeast two-hybrid system, and co-localizes with compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 93 publications
(136 reference statements)
0
27
0
Order By: Relevance
“…Viral proteins from HTLV-1, MHV, ZIKV, HCV, and CaMV confer NMD resistance by directly targeting NMD or RNA decay factors (e.g., UPF1 or the EJC) (15,16,25,29,30). However, evidence of viral proteins directly binding to viral (or nonviral) transcripts and conferring NMD resistance is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral proteins from HTLV-1, MHV, ZIKV, HCV, and CaMV confer NMD resistance by directly targeting NMD or RNA decay factors (e.g., UPF1 or the EJC) (15,16,25,29,30). However, evidence of viral proteins directly binding to viral (or nonviral) transcripts and conferring NMD resistance is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The viral core protein of Hepatitis C virus (HCV) disrupts the interaction between host protein WIBG and EJC components, attenuating NMD (29). Finally, the Cauliflower mosaic virus (CaMV) transactivator (TAV) protein interferes with the VARICOSE decapping complex, which is likely required late in the plant NMD pathway (30).…”
mentioning
confidence: 99%
“…To further investigate the ability of the 1a protein to inhibit the 2b-AGO1 interaction, we carried Complexes of the cucumber mosaic virus 1a and 2b proteins co-localize with two P-body markers. Constructs encoding either of the fluorescently tagged P-body marker proteins DCP1-RFP or DCP2-RFP [76] were expressed in N. benthamiana leaves by agroinfiltration either alone (A, B), or in leaves co-infiltrated with split YFP fusions for the CMV 1a and 2b proteins (C, D). Confocal laser scanning microscopy was used to observe the localization of DCP1-RFP and DCP2-RFP, and the YFP signal from complexes formed between sYFPn-1a and sYFPc-2b.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The strength of these countermeasures shows the size of the threat that NMD constitutes for viral replication and the place of NMD among the cellular antiviral function. Those conclusions are also supported by comparison with several other viruses, especially retroviruses and (+) RNA viruses, which RNAs are also targeted by NMD and that evolved protective means [33,[35][36][37][39][40][41][42][43]87,[125][126][127]. It is important to note that the viruses that develop a trans-inhibition process against NMD, such as HTLV-1 and potentially HIV, might only protect themselves progressively; before the viral inhibitor is expressed at an adequate level and while viral mRNA are at low level during the early phase of infection, the NMD would inhibit optimal viral replication as demonstrated with the mouse hepatitis virus (MHV, a prototypic member of the betacoronaviridae, as SARS-CoV and MERSCoV), the plant virus potato virus X (alfaflexiviridae) and turnip crinkle virus (Tombusviridae) [37,39].…”
Section: Discussionmentioning
confidence: 65%
“…The nonsense-mediated mRNA decay (NMD) pathway is an interferon (IFN) independent process that has been recently demonstrated by convergent studies to degrade several viral RNA [33][34][35][36][37][38][39][40][41], hence it can be considered as an antiviral process as well. Concerning HTLV-1, it was shown that NMD inhibition led to an upregulation in the steady state levels of all viral mRNAs, revealing a direct and/or indirect sensitivity to NMD [42].…”
Section: Trim Familymentioning
confidence: 99%